Evaluation of Bax In situ hybridization and PCNA Immunohistochemical Expression in Adenoid Cystic Carcinoma - Al-Azzawi, Lehadh Muhammed; Hussain, Qutaiba Ali (Diyala Journal of Medicine, 2019)
Background: Adenoid cystic carcinoma constitutes the second common malignant epithelial salivary gland tumour. Objective: To evaluate the expression of Bax mRNA and PCNA and to correlate between the clinicopathological features of Adenoid cystic carcinoma with expressions of Bax mRNA and PCNA protein. Materials and Methods: Nineteen formalin fixed paraffin embedded tissue blocks of Adenoid cystic carcinoma were used in this study. Bax mRNA gene was analysed by in situ hybridization techniques and PCNA was examined by immunohistochemistry. Results: In situ hybridization detection show low expression of Bax and was noted in 10 cases in Adenoid cystic carcinoma cases (52.63%), Immunohistochemical analysis show high expression of PCNA and was noted in 15 of 19 Adenoid cystic carcinoma cases (78.95 %). No significant relationship was demonstrated between Bax mRNA or the immunostaining PCNA and the morphological growth pattern or patient clinical profile. However, lymph node involvement showed statistically significant differences. Positive significant correlation was found between Bax mRNA and PCNA in Adenoid cystic carcinoma. Conclusion: The decreased expression of bax in Adenoid cystic carcinoma and high proliferative rate could explain the natural course of these tumours indicate that loss of bax expression might give the tumour cells a double growth advantage because uncontrolled proliferation is combined with reduce cell death rate.